2006
DOI: 10.1128/jvi.01049-06
|View full text |Cite
|
Sign up to set email alerts
|

Human ESCRT-II Complex and Its Role in Human Immunodeficiency Virus Type 1 Release

Abstract: The budding of many enveloped RNA viruses, including human immunodeficiency virus type 1 (HIV-1), requires some of the same cellular machinery as vesicle formation at the multivesicular body (MVB). In Saccharomyces cerevisiae, the ESCRT-II complex performs a central role in MVB protein sorting and vesicle formation, as it is recruited by the upstream ESCRT-I complex and nucleates assembly of the downstream ESCRT-III complex. Here, we report that the three subunits of human ESCRT-II, EAP20, EAP30, and EAP45, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
214
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(230 citation statements)
references
References 89 publications
(126 reference statements)
14
214
2
Order By: Relevance
“…The main discrepancy between our reconstitution and the published knockdown data is that in the latter case, essentially no budding defect is observed when ESCRT-II subunits or the most upstream ESCRT-III subunit CHMP6 are knocked down (26). In the knockdown study, protein bands for ESCRT-II EAP20/VPS25 and CHMP6 were still visible on Western blots following knockdown, and it cannot be ruled out that the residual levels of these proteins are above the threshhold needed for function.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The main discrepancy between our reconstitution and the published knockdown data is that in the latter case, essentially no budding defect is observed when ESCRT-II subunits or the most upstream ESCRT-III subunit CHMP6 are knocked down (26). In the knockdown study, protein bands for ESCRT-II EAP20/VPS25 and CHMP6 were still visible on Western blots following knockdown, and it cannot be ruled out that the residual levels of these proteins are above the threshhold needed for function.…”
Section: Discussioncontrasting
confidence: 48%
“…Consistent with the analogy to yeast ESCRTs, simultaneous knockdown of CHMP4A/B/C or CHMP2A/B reduces HIV-1 budding to the late-domain independent baseline (32). Less consistent with the yeast-based mechanism, CHMP6, CHMP3, and CHMP1A/B knockdowns have little or no HIV-1 release phenotype (26,32). These differences are hard to reconcile with live-cell imaging detecting CHMP1B at bud sites (33) and with the finding that CHMP2A and CHMP3 coassemble in vitro into tubules but do not do so on their own (34).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, studies have shown a crucial role for cholesterol-rich microdomains of the plasma membrane for shedding vesicle formation 32 as well as for biogenesis of exosomes 14 . In our in vivo experiments, we have observed a decrease in Hh signalling by knocking down Vps22, an ESCRT-II complex component described as dispensable for vesicles derived directly from the plasma membrane 33,34 , but required for MVB formation 35 (reviewed in ref. 36) supporting an MVB fusion origin.…”
Section: Discussionmentioning
confidence: 99%
“…It is also clear that not all components of the ESCRT machinery are required for virus assembly in the MVB and subsequent exocytosis. HIV-1 budding only requires TSG101 and/or ALIX, and a subset of ESCRT-III proteins (CHMP4, CHMP2 and SKD4) (Langelier, et al 2006, Morita, et al 2011. Herpes simplex virus type I production also requires a functional ESCRT-III complex, but not ALIX or TSG101, whereas Ebola virus budding requires host Vps4/SKD1 activity, but can also bypass the requirement for the TSG101 ESCRT-I component (Pawliczek andCrump 2009, Silvestri, et al 2007).…”
Section: Endocytic Trafficking and Diseasementioning
confidence: 99%